Financial Disclosure and Budgetary Practices of Religious Organization: A Study of Qaryah Mosques in Kuala Terengganu - Shahida, Shaharuddin; Maliah, Sulaiman (Gadjah Mada University, 2015)
This paper aims to examine the financial reporting and budgeting practices of qaryah mosques in Kuala Terengganu, a state in the east of Peninsular Malaysia. Data was collected using a mixed method (quantitative and qualitative) approach. The questionnaire was disseminated to qaryah mosques in Kuala Terengganu and 39 responded. To address the limitations of a questionnaire survey, semi-structured interviews were then conducted with a few of the respondents. The results revealed that qaryah mosques in Kuala Terengganu do have a satisfactory system in place in terms of their financial reporting practices. However, budgetary control practices appear to be lacking. This indicates accounting, as is practiced by qaryah mosques in Kuala Terengganu appears to be limited to financial accounting. Hence, the financial management in qaryah mosques needs to be improved so that the risk of embezzlement can be reduced.